The Effect of Resource Based View Strategy, Entrepreneurial Orientation and Innovation on Competitive Advantage in The Canteen of Universitas 17 Agustus 1945 Surabaya - Andjarwati, Tri; Oktavio, Adrie; Kaihatu, Thomas Stefanus; Nugroho, Agustinus (IJEBD (International Journal of Entrepreneurship and Business Development), 2023)
Purpose: This study aimed to test and analyze the effect of resource based view strategy, entrepreneurial orientation and innovation on competitive advantage in the canteen of Universitas 17 Agustus 1945 Surabaya. Design/methodology/approach: The saturated sample approach was applied, and as many as 44 samples or 22 canteens were acquired. SEM PLS is the analysis approach used in this study. Findings: The study's conclusions indicated that the resource based view strategy affects competitive advantage. The influence of both entrepreneurial orientation and innovation on competitive advantage has been found. Implications: The implication of this research was that business actors at the canteen of Universitas 17 Agustus 1945 Surabaya could improve the resource based view strategy, entrepreneurial orientation and innovation to increase competitive advantage; and the results of this study could complement to the study of factors that can be used to increase competitive advantage for business actors in the canteen of Universitas 17 Agustus 1945 Surabaya.